Minimising the biases in the observational study of resuscitative endovascular balloon occlusion of the aorta: a research protocol for a prospective study analysed with propensity score matching with time-varying covariates - Yosuke Matsumura; Shigeki Kushimoto; Atsushi Shiraishi (BMJ Open)
Introduction Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been used as a bridge to definitive bleeding control of subdiaphragmatic injury. Since previous observational studies have poorly adjusted for confounding factors, it is necessary to incorporate REBOA-specific and time-varying covariates in the model. We hypothesised that REBOA improves the survival of haemodynamically unstable torso trauma patients after comparing the REBOA group with a matched control group (non-REBOA group).Methods and analysis The Japanese Association for the Surgery of Trauma-REBOA Study is a prospective, multicentre, matched cohort study organised by the Clinical Trial Committee of the Japanese Association for the Surgery of Trauma. To minimise observational study biases, this study will prospectively register traumatic shock patients who require bleeding control within 60 min upon arrival at the emergency department, with in-hospital mortality as the primary outcome. After the data set is fixed, the missing values for all variables will be imputed using the multiple imputation technique. In the primary analysis, propensity scores for the probability of REBOA decision (regardless of the actual REBOA deployment) will be calculated from the baseline information using a logistic regression generalised linear mixed-effects model, which will be performed for both the REBOA use and non-REBOA use groups.Ethics and dissemination This study was approved by the ethics committee of each participating hospital. The results will be disseminated to the participating hospitals, submitted to peer-reviewed journals for publication and presented at congresses.Trial registration number UMIN Clinical Trials Registry (UMIN000035458).